Academic freedom and the role of the teaching guide at the University derived from the European Higher Education Area - Jarne Muñoz, Pablo (Revista Educación, Política y Sociedad, 2019)
This paper analyses the evolution that the academic freedom has been experiencing in our country, paying special attention to the characteristics that the European Higher Education Area has attributed to her. More specifically, along these pages there is a reflection on the impact that one of the key instruments of the EEES, the teaching guide, can develop on the academic freedom. Although it is an instrument with obvious organisational possibilities, it is necessary to consider whether its configuration is not excessively limiting in relation to the academic freedom attributed to teacher.